Identification of immunological parameters associated with the alveolar bone level in periodontal patients - Park, Chang-Seo (Korean Academy of Periodontology, 2010)
PURPOSE: The present study was performed to clarify the relationship between periodontal disease severity and selected immunological parameters consisting of serum IgG titer against periodontopathogenic bacteria, the expression of the helper T-cell cytokine by gingival mononuclear cells, and patients' immunoreactivity to cross-reactive heat shock protein (HSP) epitope peptide from P. gingivalis HSP60. METHODS: Twenty-five patients with moderate periodontitis had their gingival connective tissue harvested of gingival mononuclear cells during an open flap debridement procedure and peripheral blood was drawn by venipuncture to collect serum. The mean level of interproximal alveolar bone was calculated to be used as an index for periodontal disease severity for a given patient. Each of selected immunologic parameters was subject to statistical management to seek their correlations with the severity of periodontal disease. RESULTS: A significant correlation could not be identified between serum IgG titers against specific bacteria (Porphyromonas gingivalis, Prevotella intermedia, Fusobacterium nucleatum, Actinobacillus actinomycetemcomitans, and Streptococcus mutans) and the severity of periodontal disease. Expression of interleukin (IL)-10 by gingival mononuclear cells was statistically significant in the group of patients who had higher levels of alveolar bone height. However, a similar correlation could not be demonstrated in cases for IL-4 or interferon-γ. Patients' serum reactivity to cross-reactive epitope peptide showed a significant correlation with the amount of alveolar bone. CONCLUSIONS: It was concluded that expression of IL-10 by gingival mononuclear cells and patients' sero-reactivity to the cross-reactive HSP peptide of P. gingivalis HSP60 were significantly correlated with alveolar bone height.